Exploring gender differences in literacy and mathematical understandings in the early years of school: Can differences be explained by behaviours in the classroom? - Berthelsen, D; Walker, S (My University, 2007)
This presentation examines gender differences in language, literacy, and mathematical competence in the first years of school. The authors examined data from 'Growing Up in Australia: the Longitudinal Study of Australian Children' (LSAC), and compared Wave 2 children, who are now in year 1 of primary school, with their previous preschool results. The presentation features slides and charts outlining methodology, standard student knowledge, and assessment results for approaches to learning, learning problems, language and literacy, mathematical thinking. The study found that gender predicted performance in the first year of school, which was accounted for by gender differences in classroom behaviour, especially approach to learning.
Keywords: Education and Training; Education and Training -- Literacy and numeracy; Learning, education and training; Education and Training; Literacy and numeracy; Learning, education and training